Significance of the Vector Criterion for the Improvement of the Voting Rule - Mitev, Petar (Research Papers, 2010)
This research paper draws an approach for Pareto improvement through implementing a multicriteria rule for public choice. The main suggestion is that the political alternatives can be ranged on the basis of several criteria. For this purpose the characteristics of the political alternatives are presented with the help of the main conceptions of the characteristic theory, developed by Kelvin Lancaster. The right definition of the political alternatives in respect to the specificity of the social preferences will reduce the political externalities and this will lead to Pareto improvement. As a best approach is proposed the method of linear scalarization.